Pengaruh Shift Kerja Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening - Lavida Ramadhani; Iwang Saudji Hariyanto; Hari Purwanto; Karuniawati Hasanah (Universitas Matana, 2021)
This research aims to provide empirical evidence the influence of working shift to the employees performance, the influence of motivation to the employees performance, and the influence of working shift through motivation as intervening variable to the employees performance in emergency room of the hospitals in Madiun City. This research was conducted at emergency room of the hospitals in Madiun City. This research uses a quantitative approach to the associative design. The population of this research are employees of emergency room of the hospitals in Madiun City, namely: RSUD dr. Soedono Madiun, RSUD Kota Madiun, dan RS Paru Manguharjo, Rumah Sakit Islam Siti Aisyah Madiun, Rumah Sakit Griya Husada, Rumah Sakit Santa Clara, Rumah Sakit Ibu dan Anak Al-Hasanah, serta Rumah Sakit DKT miliki TNI Angkatan Darat, there are 155 people. The sampling technique used was total sampling. Research instrument is the questionnaire. Data analysis technique using Path Analysis. The results of the study prove that: (1) Working shift have a positive and significant effect to the employees performance in emergency room of the hospitals in Madiun City. (2) Working shift have a positive and significant effect to the employees motivation in emergency room of the hospitals in Madiun City. (3) Motivation have a positive and significant effect to the employees performance in emergency room of the hospitals in Madiun City. (4) Working shift through motivation as intervening variable does not affect have a positive and significant effect to the employees performance in emergency room of the hospitals in Madiun City. Keywords: working shift, employee performance, motivation